(untitled) (International Journal of Food and Nutritional Sciences, 2026)
Background: Vonoprazan fumarate is a potassium-competitive acid blocker (P-CAB) that inhibits the H+/K+-ATPase enzyme to suppress gastric acid secreaction and treat acid-related disorders. Materials and Methods: Vonoprazan fumarate was used for the study. HPLC grade methanol, orthophosphoric acid (OPA), and HPLC water were used to prepare the mobile phase and standard solutions. The analysis was carried out using an RP-HPLC system with a UV-PDA detector. Separation was performed on a C18 column (4.6 mm × 250 mm, 5 µm). The mobile phase consisted of methanol and 0.1% OPA in the ratio of 90:10 (v/v) at a flow rate of 1 ml/min, with detection at 254 nm. A new simple stability indicating method was developed and validate their parameters such system suitability, linearity, precision, accuracy, LOD, LOQ, robustness, assay and degradation studies by using RP-HPLC. Results and Discussion: The retention time of vonoprazan fumarate was found to be 2.6 minutes. The method showed good linearity in the concentration range of 10–50 µg/ml with a correlation coefficient (R² = 0.9999). The validation parameters and degradation studies were within acceptable limits according to ICH Q2(R1) guidelines. Conclusion: The developed method consumes nearly 20% less mobile phase as compared to the already reported methods, making it economical and environmentally friendly for routine analysis of vonoprazan fumarate in API and dosage forms.